Optimizing Work Engagement to Reduce Burnout: The Influence of Job Crafting and Organizational Culture in the Workplace - Rizal, Muchammad; Pratitis, Niken Titi; Noviekayati, IGAA (Insight: Jurnal Ilmiah Psikologi, 2025)
Burnout is the result of long-term, poorly managed stress, which eventually leads to physical exhaustion. In corporate environment, burnout is a serious problem that needs special attention because it not only impacts the health and well-being of employees, but also directly affects productivity, performance, and the sustainability of company operations. Employees who apply job crafting by proactively adjusting tasks, work relationships, and perspectives on work to align with their abilities and resources are less likely to experience burnout, because they can create a work environment that is more meaningful and suits their personal needs. A positive and supportive organizational culture plays an important role in reducing employee burnout. Work engagement also found to be able to decrease burn out.  However, the mechanism of their influences on burn out still needs to be understood.  This study aims to analyze the relationship between job crafting, organizational culture and burn out through work engagement as a mediator. The research subjects involved 106 employees from two state-owned companies, namely PT X in Sidoarjo and PT Z in Surabaya, Indonesia. A path analysis conducted using JASP for Windows. The results show that work engagement mediates the relationship between job crafting, organizational culture, and burnout. In conclusion, employees who are active in job crafting and have a positive view of the company culture and values tend to have higher work engagement, which in turn make employees less likely to experience burnout. This study findings provide new understanding on how company can prevent employees burnout.